ATR-FTIR spectroscopy combined with multivariate analysis as a rapid tool to infer the biochemical composition of Ulva laetevirens (Chlorophyta) - Derksen, Goverdina C. H.; Blommaert, Lander; Bastiaens, Leen; Hasşerbetçi, Cem; Fremouw, Roy; van Groenigen, Jesse; Twijnstra, Robert H.; Timmermans, Klaas R. (Frontiers in Marine Science, 2023)
ATR-FTIR analysis is a rapid tool and represents a snapshot of all molecules present in a (plant) sample. Most alternative techniques for biochemical analyses of plant biomass require destructive sampling, complex and laborious sample pre-treatment and precise and costly analysis. These analyses are often limited to soluble compounds instead of all compounds present. Such complicated procedures are not efficient for manipulative studies that involve repeated sampling and rapid nutrient changes over time, such as in agro-industrial cultivation studies. In our study, the green seaweed species Ulva laetevirens (Chlorophyta) was cultivated under different nutritional regimes in on-shore cultivation tanks. The regimes were nitrogen and phosphorous replete, nitrogen-deplete, phosphorous-deplete and light limited. Samples were taken and tested according to common laborious analysis methods to determine the biochemical composition of polysaccharides, proteins, carbon and nitrogen. These results were compared with the potential of ATR-FTIR spectroscopy combined with multivariate analysis to allow for prediction of biomass composition. Statistical analysis of the spectra showed that the samples were clustered according to the nutritional regime during the incubation of U. laetevirens. This made it possible to deduce which abiotic factors were replete or deplete during cultivation. Furthermore, partial least square regression analysis proved the most suitable method to predict carbohydrate concentration and nitrogen content present in the biomass. Based on these findings, it is concluded that ATR-FTIR spectroscopy is an efficient and rapid alternative tool for qualitative and quantitative determination of the biochemical composition of U. laetevirens, that can be used in industrial cultivation setups.